Antibacterial potential of silver–selenium nanocomposites in mitigating fire blight disease in Pyrus communis L - Imran, Muhammad; Umer, Muhammad; Iqbal Raja, Naveed; Abasi, Fozia; Sardar, Nimra; Rahman, Ubaidur; Naqvi, Syed Azaz Mustafa; Baloch, Muhammad Yousuf Jat; Alrefaei, Abdulwahed Fahad (Frontiers in Plant Science, 2025)
Pyrus communis L. is a vital fruit tree known for its nutritional and economic importance. Thus, for humans, it is an essential element for their balanced nutritional diet, as it contains the major dietary fibers, vitamins, and minerals. All of these nutritionally important aspects decrease with the impact of disease fire blight. Erwinia amylovora is a causative agent of fire blight. This infection causes a considerable loss in the production of Pyrus communis L. Annually, approximately 50% of pear fruit in Pakistan is misplaced because of these illnesses. Therefore, we propose nanotechnology remediation to treat pear plants and obtain the desired yield. In this regard, an experiment was designed to treat infected plants with different concentrations of silver–selenium nanocomposites, which was based on a literature review that indicated the antimicrobial activities of silver and selenium nanoparticles. Silver–selenium nanocomposites were prepared using a green synthesis method, and their synthesis was confirmed using characterization techniques. The experiment was performed at a farmhouse in Chakwal district, Punjab, Pakistan. The experimental results showed increased morphological, physiological, and biochemical parameters. In this regard, the best treatment remained at 50 ppm for the Ag–Se nanocomposite, which improved the plant in different aspects. At the same time, they have improved fruit metrics, such as vitamin C, pH, and juice content. Thus, these results show a possible improvement in enhancing the resistance against fire blight by using green-synthesized Ag–Se NCs. Further studies are needed to understand fully the molecular mechanisms and actions of Pyrus communis L. in treating fire blight disease and to establish the optimal treatment plan.